Investigating impulse buying and variety seeking: towards a general theory of Hedonic Purchase Behaviors - Marshall, R; Sharma, P; Sivakumaran, B (Association for Consumer Research, 2006)
Although impulse buying (IB) and variety seeking (VS) are both low-effort feelings-based behaviors with similar underlying psycho-social processes, there is no general theory to explain such hedonic purchase behaviors. This paper explores similarities and differences between these behaviors using a conceptual framework incorporating three relevant consumer traits – consumer impulsiveness, optimum stimulation level and self-monitoring. The findings from two studies across student and retail customer samples, show that consumer impulsiveness and optimum stimulation level influence both behaviors positively, whereas self-monitoring influences IB negatively and VS positively. Self-monitoring also moderates the influence of consumer impulsiveness and optimum stimulation level on purchase decisions, negatively for IB and positively for VS.
Keywords: No keywords